JAPAN IN INTERNATIONAL CAPITAL MOVEMENT - S. M. Rebrey (Vestnik MGIMO-Universiteta)
Japan, the largest net exporter of investment plays one of key roles in the in-ternational capital flows and has a serious impact on the global trends in this important dimension of international economic relations. Vast amounts of for-eign direct investment (FDI) outflow are important for the Japanese national economy as well, since Japanese overseas production in some areas reaches 40% and is an important part of its industrial potential. However, FDI inflow remains low, indicating an unbalanced participation of Japan in the international capital flows. Japan in international capital flows presents a field for complex numerous research. This article concentrates on analysis of dynamics and geographical structure of capital flows, reveal the trends, and estimate the effect of Abenomics.